Patterns of Street Food Purchase in Cities From Central Asia - Sousa, Sofia; Lança de Morais, Inês; Albuquerque, Gabriela; Gelormini, Marcello; Casal, Susana; Pinho, Olívia; Motta, Carla; Damasceno, Albertino; Moreira, Pedro; Breda, João; Lunet, Nuno; Padrão, Patrícia (Frontiers in Nutrition, 2022)
Street food makes a significant contribution to the diet of many dwellers in low- and middle-income countries and its trade is a well-developed activity in the central Asian region. However, data on its purchase and nutritional value is still scarce. This study aimed to describe street food purchasing patterns in central Asia, according to time and place of purchase. A multicentre cross-sectional study was conducted in 2016/2017 in the main urban areas of four central Asian countries: Dushanbe (Tajikistan), Bishkek (Kyrgyzstan), Ashgabat (Turkmenistan) and Almaty (Kazakhstan). Street food markets (n=34) and vending sites (n=390) were selected by random and systematic sampling procedures. Data on the purchased foods and beverages were collected by direct observation. Time and geographic location of the purchases was registered, and their nutritional composition was estimated. A total of 714 customers, who bought 852 foods, were observed. Customers’ influx, buying rate and purchase of industrial food were higher in city centres compared to the outskirts (median: 4.0 vs. 2.0 customers/10min., p<0.001; 5.0 vs. 2.0 food items/10min., p<0.001; 36.2% vs. 28.7%, p=0.004). Tea, coffee, bread and savoury pastries were most frequently purchased in the early morning, bread, main dishes and savoury pastries during lunchtime, and industrial products in the mid-morning and mid-afternoon periods. Energy and macronutrient density was highest at 11:00-12:00 and lowest at 09:00-10:00. Purchases were smaller but more energy-dense in city centres, and higher in saturated and trans-fat in the peripheries. This work provides an overview of the street food buying habits in these cities, which in turn reflect local food culture. These findings from the main urban areas of four low- and middle-income countries which are currently under nutrition transition can be useful when designing public health interventions customised to the specificities of these food environments and their customers.